A mild extraction and separation procedure of polysaccharide, lipid, chlorophyll and protein from Chlorella spp. (April 2018) - Zhao, Wenhuan; Duan, Meirong; Zhang, Xu; Tan, Tianwei
Abstract: This study developed a way to separate lipid, polysaccharide, protein and chlorophyll from wet Chlorella spp. (85% moisture content, wt) by using three-phase partitioning (TPP). The optimum conditions for the key steps were researched and defined as (I) cell disruption at the following conditions: biomass concentration 20 g/L, bath temperature 90 °C, duration 2.5 h, enzyme concentration 12 g/L, enzyme hydrolysis time 4 h; and (II) TPP at 40% (NH4 )2 SO4 (wt, %), sample solution/t-butanol 1: 2 (V/V), room temperature. The extraction yield of lipid and the poysaccharide preservation rate by the optimized procedure were 80.24%, 90.63%, respectively. The protein removal rate was 78.87%. The results provided a promising towards the industrial separation of lipid, polysaccaride, protein and chlorophyll. Graphical abstract: Highlights: A method to extract and separate active components from Chlorella spp. is proposed. The process involves a mild cell disruption. Utilization of active components of Chlorella spp. improves the economic feasibility.